Human immune responses to Burkholderia pseudomallei characterized by protein microarray analysis. - Suwannasaen, D; Mahawantung, J; Chaowagul, W; Limmathurotsakul, D; Felgner, P; Davies, H; Bancroft, G; Titball, R; Lertmemongkolchai, G (2011)
BACKGROUND: We aimed to determine the antibody and T cell responses to Burkholderia pseudomallei of humans to select candidate vaccine antigens. METHODS: For antibody profiling, a protein microarray of 154 B. pseudomallei proteins was probed with plasma from 108 healthy individuals and 72 recovered patients. Blood from 20 of the healthy and 30 of the recovered individuals was also obtained for T cell assays. RESULTS: Twenty-seven proteins distinctively reacted with human plasma following environmental exposure or clinical melioidosis. We compared the responses according to the patient's history of subsequent relapse, and antibody response to BPSL2765 was higher in plasma from individuals who had only 1 episode of disease than in those with recurrent melioidosis. A comparison of antibody and T cell responses to 5 B. pseudomallei proteins revealed that BimA and flagellin-induced responses were similar but that BPSS0530 could induce T cell responses in healthy controls more than in recovered patients. CONCLUSIONS: By combining large-scale antibody microarrays and assays of T cell-mediated immunity, we identified a panel of novel B. pseudomallei proteins that show distinct patterns of reactivity in different stages of human melioidosis. These proteins may be useful candidates for development of subunit-based vaccines and in monitoring the risks of treatment failure and relapse.